Supply Shocks in the Market for Apprenticeship Training. (February 2022) - Muehlemann, Samuel; Dietrich, Hans; Pfann, Gerard; Pfeifer, Harald
Highlights: Positive supply shock increases the number of new apprenticeship contracts Wage rigidity in the German apprenticeship market No evidence for substitution effects by the education level of apprentices Abstract: We present a model with heterogeneous inputs and constant elasticity of substitution to examine the possible effects of a supply shock in the market for apprenticeship training. The model's predictions are tested using data from a German high school reform that led to a one-time increase in the supply of highly educated apprentices. A difference-in-differences estimation strategy exploits regional variation in the timing of implementation, and an instrumental variable approach identifies the supply shock effects. We find that apprenticeship contracts among individuals with a high school degree increased by 7%, while apprentice wages were unaffected by the supply shock. Moreover, we find no evidence of substitution effects, as the number of training contracts among individuals with a lower-level school degree did not decrease. Our model predicts that such effects may occur when wages are sticky for apprentices with a high level of education relative to their productivity, which signals inefficiencies in the market for apprenticeship training.